Beyond the neoliberal creative city: Critique and alternatives in the urban cultural economy - Hollands, Robert G. (Bristol Bristol University press, 2024)
A buoyant, creative economy can be seen as the saviour of many cities, but behind such 'urban makeovers' lie serious problems such as widening inequalities and gentrification. Blending lively city case studies with broader theoretical debates, this book explores the opportunities for a more just and sustainable urban future